2013
DOI: 10.1051/kmae/2013038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improved bottom hypoxia on zooplankton community in shallow eutrophic lake

Abstract: Key-words:oxygen condition, hypoxia, zooplankton, copepod, brackish lakeWe followed changes in the abundance of meso-and microzooplankton after an existing bottom hypoxia improved by the introduction of water with high oxygen content into the bottom. Mesozooplankton, calanoid copepod Acartia hudsonica showed ten times higher abundance under high oxygen condition at the bottom than under control where there was less oxygen at the bottom. On the other hand, during summer when microzooplankton such as rotifers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…This is consistent with our results, which showed that most rotifers seemed to prefer low oxygen conditions, and the smaller Cladocera were more resistant to oxygen depletion than the larger daphnids. The results from field studies also suggest that decreased meta-and hypolimnetic oxygen concentrations resulted in a shift in zooplankton from large to smaller species [14,18,19]. We observed a similar pattern of changes in zooplankton community structure as a result of oxygen stress, regardless of trophic status, which indicated that oxygen stress is one of the most important factors altering zooplankton structures.…”
Section: Discussionsupporting
confidence: 72%
“…This is consistent with our results, which showed that most rotifers seemed to prefer low oxygen conditions, and the smaller Cladocera were more resistant to oxygen depletion than the larger daphnids. The results from field studies also suggest that decreased meta-and hypolimnetic oxygen concentrations resulted in a shift in zooplankton from large to smaller species [14,18,19]. We observed a similar pattern of changes in zooplankton community structure as a result of oxygen stress, regardless of trophic status, which indicated that oxygen stress is one of the most important factors altering zooplankton structures.…”
Section: Discussionsupporting
confidence: 72%
“…The effect seems to be the result of the fact that the presence of meta- and hypolimnetic hypoxia decreased the mean depth selected by Daphnia but not by the fish. The greater predation rate of the fish in hypolimnetic hypoxia confirmed the results of outdoor enclosure experiments (Wright and Shapiro, 1990; Field and Prepas, 1997; Chang et al ., 2013) but contradicts the results from the single indoor experiment (Larsson and Lampert, 2011). Two possible explanations for the opposing results are most likely.…”
Section: Discussionsupporting
confidence: 76%
“…Experimental evidence is less consistent. While three field studies confirmed that decreased meta- and hypolimnetic oxygen concentrations resulted in a shift from large- to intermediate-bodied Daphnia (Wright and Shapiro, 1990; Field and Prepas, 1997; Chang et al ., 2013), a single indoor study (Larsson and Lampert, 2011) revealed the opposite effect, which was attributed to a decreased mortality risk in the presence of metalimnetic hypoxia, because Daphnia is more tolerant of lower oxygen concentrations than most pelagic fish species (Weider and Lampert, 1985; Klumb et al ., 2004; Stanley and Wilson, 2004; Vanderploeg et al ., 2009a, 2009b). However, the experimental design of the study conducted by Larsson and Lampert (2011) did not allow verification of the possibility that either the fish’s acclimation to hypoxia or the shrinking thickness of the metalimnion (due to the increased temperature of the epilimnion) would increase the mortality risk caused by planktivorous fish at a low oxygen concentration in the metalimnion.…”
Section: Introductionmentioning
confidence: 98%